EFEKTIVITAS PENANGANAN SAMPAH DI KABUPATEN SUMEDANG - edi setiawan; Amalia Syarafinawati; Apit Yuli; Dewi Dahliawati; Puput Vena Pitriani; Rohmana (JRPA - Journal of Regional Public Administration, 2022)
Thisstudy aimstodetermine andanalyze the effectivenessofwaste management ofSumedangRegency. The methodusedinthe preparationofthis researchisaqualitativeresearchmethodwithindependent variables,namely:theeffectivenessofwastemanagement.Thesamplingtechnique usedispurposive sampling.Researchinformantsare: HeadofService,General Affairs and Personnel Division, Program, Evaluation and Reporting Division, PlanningandCapacityBuildingDivision,GarbageManagementandLandscaping Divisionasmany as5people.Meanwhile,inanalyzingthe data,the Milesand Hubermanmodelswereusedwiththe followingsteps: datareduction,data presentation, conclusiondrawing and triangulation techniques.Basedontheresultsofthestudythattheeffectivenessofwastehandling in the PSP(Waste Managementand Landscaping)Divisionofthe Environmentand Forestry OfficeofSumedangRegency,itcanbeseenfrom eachdimensionand indicator oforganizationalcharacteristics, environmentalcharacteristics,worker characteristics,andmanagementcharacteristicsthathave beencarriedoutwell. Activitiesinthe programsthathavebeencarriedoutcanachieve theinitial objectivesofthe program.where eachimplementationisdirectedatthe driving force ofthe organizationitself,namely humanswithcertaingoalssothatwhatis theorganization'sgoalscanbeachievedproperly,effectivelyandefficiently,where initsimplementationrequirestime andprocessesthatare directedtobuildand makeit better. Suggestionsthatthe developmentofemployeesatthe Departmentof EnvironmentandForestry ofSumedangRegency are directedtocreateamore efficient,effective,cleanandauthoritativeapparatusandbeabletocarry outall generalgovernmenttasksaswellaspossible basedonthe spiritandattitude of serviceto thecommunity,nation and state.